2001
DOI: 10.1542/peds.108.5.e83
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine in the Treatment of Children and Adolescents With Attention-Deficit/Hyperactivity Disorder: A Randomized, Placebo-Controlled, Dose-Response Study

Abstract: ABSTRACT. Objective. Atomoxetine is an investigational, nonstimulant pharmacotherapy being studied as potential treatment for attention-deficit/hyperactivity disorder (ADHD). It is thought to act via blockade of the presynaptic norepinephrine transporter in the brain. We assessed the efficacy of 3 doses of atomoxetine compared with placebo in children and adolescents with ADHD.Methods. A total of 297 children and adolescents who were 8 to 18 years of age and had ADHD as defined by the Diagnostic and Statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
391
4
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(427 citation statements)
references
References 20 publications
25
391
4
7
Order By: Relevance
“…Atomoxetine is a development candidate for pharmacotherapy of ADHD and has been shown in early studies to be efficacious and well-tolerated for use in this disorder Michelson et al 2001). We propose that the atomoxetine-induced increase of DA EX and NE EX in the PFC, and presumably other cortical areas, enhances catecholaminergic neurotransmission in the cortex and this may be a mechanism of action of atomoxetine in the pharmacotherapy Figure 5.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Atomoxetine is a development candidate for pharmacotherapy of ADHD and has been shown in early studies to be efficacious and well-tolerated for use in this disorder Michelson et al 2001). We propose that the atomoxetine-induced increase of DA EX and NE EX in the PFC, and presumably other cortical areas, enhances catecholaminergic neurotransmission in the cortex and this may be a mechanism of action of atomoxetine in the pharmacotherapy Figure 5.…”
Section: Discussionmentioning
confidence: 96%
“…In children and adolescents, atomoxetine had superior outcomes in reducing ADHD symptoms compared with placebo and had a graded dose response (Michelson et al 2001). Atomoxetine significantly reduced core symptoms of ADHD in an openlabel study in children .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The power calculations for designing the study were based on research in children and adolescents that suggested atomoxetine has an effect size of 0.7 for ADHD 27 and indicated that 35 subjects per group would provide 80% power to detect that effect size at a significance level of 0.05. At trial completion, the variability estimates from the final model indicated that the obtained sample size (35 per group) provided 80% power to detect a difference between groups in DSM-IV ADHD score of at least 9.9 as significant.…”
Section: Patient Dispositionmentioning
confidence: 99%
“…Atomoxetine is reported to be highly effective, yet produce few side effects and be devoid of abuse liability (Heil, 2002;Michelson et al, 2001Michelson et al, , 2002Spencer et al, 1998). Atomoxetine is a selective norepinephrine transporter inhibitor with a relatively low affinity for serotonin and dopamine uptake processes and with minimal affinity for other biological binding sites (Bymaster et al, 2002).…”
Section: Introductionmentioning
confidence: 99%